HUBUNGAN KETERAMPILAN MENGAPRESIASI PUISI DENGAN KETERAMPILAN MENULIS PUISI SISWA KELAS VIII SMP MUHAMMADIYAH 6 PADANG - Gusni, Lisa; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by several factors. The first factor,facilities and infrastructure to support the learning for still there even less. Second, students skill in writing poetry is low. This research aims to describe the things. First, the skills to appreciate poetry class VIII SMP Muhammadiyah 6 Padang. Second, skill writing poetry students class VIII SMP Muhammadiyah 6 Padang. Third, the relationship skills to appreciate poetry and writing poetry students class VIII SMP Muhammadiyah 6 Padang.                       This research uses a quantitative approach with a descriptive menthod through correlational approach. Sample of this research were students class VIII SMP Muhammadiyah 6 Padang enrolled in the academic year 2012/2013 which is spread in 3 class. Taking random sample totaling 28 students. The data is a result of research skills of student class VIII SMP Muhammadiyah 6 Padang to appreciate poetry gained through objective test and the result writing poetry students class VIII SMP Muhammadiyah 6 Padang obtained through performance test.             Based on the data processing and discussion, obtained the following result. First, the average skill level to appreciate poetry of students class VIII SMP Muhammadiyah 6 Padang are enough qualifying (61,03). Second, the average writing poetry students class VIII SMP Muhammadiyah 6 Padang are more than enough in qualifying (66,64). Third, there is a significant positive the significant level of  95%  is equal to 1,706 between appreciating poetry skills with writing poetry.